2005
DOI: 10.1038/sj.cdd.4401779
|View full text |Cite
|
Sign up to set email alerts
|

Challenge and promise: roles for clusterin in pathogenesis, progression and therapy of cancer

Abstract: Clusterin (CLU) has been implicated in various cell functions involved in carcinogenesis and tumour progression. There are two known CLU protein isoforms generated in human cells. A nuclear form of CLU protein (nCLU) is proapoptotic, and a secretory form (sCLU) is prosurvival. CLU expression has been associated with tumorigenesis of various malignancies, including tumours of prostate, colon, and breast. Furthermore, CLU expression is modulated by many factors that are believed to regulate tumour growth and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
278
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(292 citation statements)
references
References 50 publications
9
278
2
3
Order By: Relevance
“…23,24 The precise physiological role of clusterin is unknown, although a large diversity of functions has been suggested. 25 In particular, it has been shown that the chaperone behavior of clusterin can be observed in vitro and appears similar to that described for the small heat shock proteins. 26,27 Clusterin has been reported to inhibit in vitro fibril formation by a number of proteins and peptides linked to aggregation diseases including the Aβ peptide, apo C-II, and the prion neuropeptide 106-126.…”
Section: Introductionmentioning
confidence: 83%
“…23,24 The precise physiological role of clusterin is unknown, although a large diversity of functions has been suggested. 25 In particular, it has been shown that the chaperone behavior of clusterin can be observed in vitro and appears similar to that described for the small heat shock proteins. 26,27 Clusterin has been reported to inhibit in vitro fibril formation by a number of proteins and peptides linked to aggregation diseases including the Aβ peptide, apo C-II, and the prion neuropeptide 106-126.…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, it has been proposed to be a potential diagnostic and prognostic marker for colon carcinoma aggressiveness. 66 WFDC2 is known to be overexpressed in a number of cell lines, including ovarian, renal, lung, colon, and breast. The bulk of initial studies on WFDC2 were focused on using it as a biomarker for ovarian carcinoma.…”
Section: Identification Of Proteins Known To Be Associated With Cancersmentioning
confidence: 99%
“…3 It is encoded by a single-copy gene located on chromosome 8p21-p12. However, CLU expression is complex, appearing as different forms in different cell compartments.…”
mentioning
confidence: 99%